2019
DOI: 10.7441/joc.2019.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Green Supply Chain Initiatives and their Impact on Economic Performance of Firms: Evidence from Pakistan’s Manufacturing Sector

Abstract: The adoption and implementation of green supply chain management (GSCM) initiatives within an organization have been claimed to create specific ecological, competitiveness and monetary benefits. This study explores the drivers of GSCM initiatives and their effect on the economic performance of manufacturing companies in three sectors (textile, chemical, and pharmaceutical) of Pakistan's economy. The three driver social pressure, competitive pressure, and institutional pressure were chosen as the enablers of GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In terms of discussing the impact of environmental determinants on the performance of food producers and foodstuff trade, i.e., food availability and partial food access, Morkūnas, Volkov, and Pazienza [14], Morkūnas et al [15], and Tomchuk et al [16] mentioned that economic and environmental factors have an impact for resilience of agricultural enterprises. Similarly, Handayani, Wahyudi, and Suharnomo [17], Mikhaylova et al [18], Akhtar [19], Kheyfets and Chernova [20], Stjepanović, Tomić, and Škare [21], Cismas et al [22], Jayasundera [23], and Harold [24] proved that green innovations positively influence business performance, sustainability of agriculture, and food security. Haninun, Lindrianasari, and Denziana [25] mentioned that environmental performance has an effect on financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of discussing the impact of environmental determinants on the performance of food producers and foodstuff trade, i.e., food availability and partial food access, Morkūnas, Volkov, and Pazienza [14], Morkūnas et al [15], and Tomchuk et al [16] mentioned that economic and environmental factors have an impact for resilience of agricultural enterprises. Similarly, Handayani, Wahyudi, and Suharnomo [17], Mikhaylova et al [18], Akhtar [19], Kheyfets and Chernova [20], Stjepanović, Tomić, and Škare [21], Cismas et al [22], Jayasundera [23], and Harold [24] proved that green innovations positively influence business performance, sustainability of agriculture, and food security. Haninun, Lindrianasari, and Denziana [25] mentioned that environmental performance has an effect on financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hypothesis 4 of the study stating that Environmental sustainability elements in SCM (ES) have a positive effect on the Operation Capabilities (OC) of the company SCM was accepted since (β = 0.569, p-value < 0.5). This implies that sustainability factors based on environmental factors are an important part of the modern supply chain, as supported byAkhtar (2019). The results also indicated that social aspects of sustainability in SCM (SA) have a positive effect on the Operation Capabilities of the company SCM (β = 0.285, p-value < 0.5).…”
mentioning
confidence: 58%
“…The significance and relevance of adopting and implementing sustainable supply chain management initiatives as economic drivers have created ecological, competitive, and financial incentives for those involved (Akhtar, 2019). Sustainability in supply chain management involves incorporating environmentally viable practices from the product design and development to final consumption by the end-user.…”
Section: Environmental Sustainability Elements In Supply Chain Manage...mentioning
confidence: 99%
“…However, from an environmental perspective, industrial growth is notable for adversely influencing climate conditions [7][8][9]. Many investigations have highlighted the growing problems due to environmental degradation.…”
Section: Introductionmentioning
confidence: 99%